Confirmation of association of chromosome 5q31-33 with United Kingdom Caucasian Graves' disease. - Simmonds, M; Yesmin, K; Newby, P; Brand, O; Franklyn, J; Gough, S (2010)
BACKGROUND: Previous genome-wide microsatellite screening in Graves' disease (GD) has suggested several regions of linkage to disease. Although replication has been inconsistent, some regions such as chromosome 5q31-33 have been associated with several Oriental GD patient cohorts. Recently, two studies have reported association of single-nucleotide polymorphism (SNP) rs31480 in interleukin 3 (IL-3) and the rs1368408 and SNP75 (-623 approximately -622 AG/-T) SNPs in secretoglobulin family 3a member 2 (SCGB3A2) with GD and suggested that this may account for linkage to the 5q31-33 region in Oriental GD datasets. We sought to confirm this association in a large Caucasian U.K. GD cohort. METHODS: The rs31480 SNP was shown to tag all known common variations in IL-3 and the rs1368408 SNP was shown to tag all common variations in SCGB3A2. The SCGB3A2 SNP75 was found to be rare in the U.K. Caucasian population and, therefore, was not screened. We genotyped rs31480 and rs1368408 and performed a case-control association study in 2504 GD cases and 2688 controls from the U.K. RESULTS: Association between the SCGB3A2 rs1368408 SNP and GD was detected (p = 0.007, odds ratio = 1.18, 95% confidence intervals = 1.05-1.33). No association between the IL-3 rs31804 SNP and U.K. Caucasian GD patients was observed. CONCLUSIONS: These data suggest that chromosome 5q31-q33 contains a susceptibility locus for Caucasian GD patients as well as Oriental GD patients. Although association was detected between SCGB3A2 and U.K. Caucasian GD subjects, the size of effect was smaller than that seen in the Oriental population (odds ratio = 1.28-1.73). Fine mapping within this region will be required to determine the exact location of the etiological variants present within this region for both Caucasian and Oriental GD patients.